The new American diner cookbook : classic and new favorites from (and inspired by) diners across the U.S.A. - Roberts, Julissa Hernández (Harvard Common Press, an imprint of The Quarto Group, 2026)
"The New American Diner Cookbook brings the soul-warming comfort of classic American diner foods into your kitchen, updating beloved favorites with fresh ingredients and modern twists while keeping all the nostalgic charm intact"-- Provided by publisher.